Structures of substrate- and product-bound forms of a multi-domain copper nitrite reductase shed light on the role of domain tethering in protein complexes. (2020) - Sasaki, Daisuke; Watanabe, Tatiana F.; Eady, Robert R.; Garratt, Richard C.; Antonyuk, Svetlana V.; Hasnain, S. Samar
No abstract available